Immunohistochemical expression of cyclooxygenase-2 in oral lichen planus and normal oral mucosa - Tibin K Baby; P R Bindhu; Rekha Krishna Pillai; P Jayanthi (Wolters Kluwer Medknow Publications, 2022)
Background: Oral lichen planus (OLP) is a chronic inflammatory disease for which the pathogenesis is complex and not fully understood; autoimmunity has been suggested as a causative factor. World health organization (WHO) has classified OLP as a potentially malignant lesion. Cyclooxygenase-2 (COX-2) is an inducible key enzyme that generates prostanoids which play a critical role in inflammation, immunopathology; also considered as a malignant potential marker. Aims: The present study was conducted to analyze and compare epithelial COX-2 expression in OLP clinical subtypes and normal oral mucosa to evaluate its role in the pathophysiology of the disease process. Methods: This retrospective immunohistochemistry (IHC) study was performed on tissue sections of 30 OLP and 10 normal oral mucosae for COX-2 expression. Statistical Analysis Used: Descriptive and comparative statistical methods were done using 'one-way Analysis of Variance (ANOVA), 't' and Chi-square tests. Results: All the OLP showed epithelial COX-2 expression; strong expression was noted in 80% of the OLP while normal oral mucosa sections showed no expression. Cox-2 expression was significantly higher in erosive lichen planus compared to reticular lichen planus. Conclusions: Strong expression of COX-2 in OLP suggested its important role in pathogenesis. Although COX-2 has been connected to malignant development and autoimmunity, as the malignant development in OLP is quite rare, this study suggests that increased levels of COX-2 seen here may support an autoimmune cause of the disease process.